HISTORICAL ROOTS OF THE UZBEK LANGUAGE - Qodirova Gulnoza Solixudjayevna (Journals Park Publishing, 2022)
The article talks about the development of the ancient Uzbek language and its refinement over the centuries.
Keywords: language, historical grammar, lexicon, uzbek, turk, subject, object.